Relationship Between Liver Function Tests & Cardiovascular Risk Factors in Stage 3-5 Pre-Dialysis Chronic Kidney Disease - Khalid Shehzad, Obaid Ur Rehman, Aurangzaib Khan, Munaza Khattak, Siyab Ahmed, Khalid Shehzad, Shabir Ahmed Orakzai (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The main objective of this study was to evaluate the relation between liver function tests and biochemical cardiovascular risk factors in chronic kidney disease patients. Methodology: this study was conducted in Khyber Teaching Hospital Peshawar, from Ist May 2022 till 31st Oct, 2022. 250 patients in total were included in this study. All the people included in this study were chronic kidney disease patients at pre dialysis stage 3 to 5. Data collected included demographic information, liver function tests and biochemical cardiovascular risk factors. CKD-EPI equation was used to calculate glomerular filtration rate. Results: This study resulted in ALT being negatively correlated with C reactive protein and intact level of parathyroid hormone and positively correlated with glomerular filtration rate, triglyceride, calcifediol and albumin. Gamma-glutamyl transferase was negatively correlated with HDL cholesterol and positively correlated with glomerular filtration rate, triglycerides and C reactive protein. AST was negatively correlated with C reactive protein and intact level of parathyroid hormone and positively correlated with glomerular filtration rate, HDL cholesterol, albumin and calcifediol. In diabetic patients AST and ALT were positively correlated with glomerular filtration rate, additionally AST was also positively correlated with HDL cholesterol but negatively with intact parathyroid hormone. Gamma-glutamyl transferase had no correlation. In total population of the study and in diabetic group correlation analysis was run between glomerular filtration rate and biochemical cardiovascular risk factors, it resulted in GFR being negatively correlated with albuminuria, C reactive protein and intact parathyroid hormone and positively correlated with triglyceride, calcifediol and albumin. A partial correlation analysis, controlled for GFR, was also run between cardiovascular risk factors and LFTs. It resulted in no correlation between both. Practical implication: this study could be useful when planning the treatment of CKD patients with cardiovascular risk factors. Also in predicting the risk of cardiovascular disease in CKD patients based on the LFTs. It could also help initiate further reseach on related topics like the role of LFTs in predicting cardiovascular disease in CKD patients. Conclusion: this study concluded that relation between liver function tests and biochemical cardiovascular risk factors in chronic kidney disease patients could be the function of compromised glomerular filtration rate. Keywords: cardiovascular risk factors, chronic kidney disease, aspartate transaminase, gamma-glutamyl transferase, alanine transaminase